Impact of a Recreationally Oriented Psychological Guidance Program Using Selected Small-Game Activities on Enhancing Psychological Energy and Acquiring Selected Ball-Handling Skills in Rhythmic Gymnastics Among Female Students - Salman, Suhair Rahman (JURNAL PENDIDIKAN OLAHRAGA, 2025)
The Problem. Rhythmic gymnastics is an individual sport with complex physical and skill requirements, making the process of learning its skills require increased educational and training efforts. Since recreational guidance sessions improve psychological and behavioral responses and accelerate the acquisition of motor skills, the researcher decided to use recreational sessions, based on some small games, to develop psychological energy and learn some ball skills in rhythmic gymnastics. Objectives. The most important of these were to identify the effect of a recreational psychological guidance program based on some small games on developing psychological energy and learning some ball skills in rhythmic gymnastics for female students between the pre- and post-tests. Also, to identify differences in the psychological energy scale and the level of learning some ball skills in rhythmic gymnastics for female students between the two research groups (experimental and control) in the post-tests. Materials and Methods. To achieve the objectives, the researcher used an experimental approach with two groups, an experimental and a control, and a descriptive approach for measuring numbers. The population consisted of (122) second-year female students in the College of Physical Education (Dhi Qar University and Al-Ain University) for the academic year (2024-2025). The applied sample consisted of (40) female students divided into a control group implementing the college's curriculum, and an experimental group implementing the same curriculum with recreational guidance sessions at the beginning of the main semester. Results: The experimental group outperformed the control group on the psychological energy scale and learning the ball skills under study.Conclusions: The use of small games within the program contributed to creating a stimulating and interactive learning environment, which enhanced the level of psychological acceptance and positive interaction among students with rhythmic gymnastics activities. Using the program led to a noticeable improvement in learning ball skills in gymnastics, as a result of the balanced integration of psychological and skill aspects.